Didn't we almost have it all : in defense of Whitney Houston - Kennedy, Gerrick (Abrams Press, 2022)
"A candid exploration of the genius, shame, and celebrity of Whitney Houston a decade after her passing. On February 11, 2012, Whitney Houston was found submerged in the bathtub of her suite at the Beverly Hilton Hotel. In the decade since, the world has mourned her death amid new revelations about her relationship to her Blackness, her sexuality, and her addictions. Didn't We Almost Have It All is author Gerrick Kennedy's exploration of the duality of Whitney's life as both a woman in the spotlight and someone who often had to hide who she was. This is the story of Whitney's life, her whole life, told with both grace and honesty. Long before that fateful day in 2012, Whitney split the world wide open with her voice. Hers was a once-in-a-generation talent forged in Newark, NJ, and blessed with the grace of the church and the wisdom of a long lineage of famous gospel singers. She redefined 'The Star-Spangled Banner.' She became a box-office powerhouse, a queen of the pop charts, and an international superstar. But all the while, she was forced to rein in who she was amid constant accusations that her music wasn't Black enough, original enough, honest enough. Kennedy deftly peels back the layers of Whitney's complex story to get to the truth at the core of what drove her, what inspired her, and what haunted her. He pulls the narrative apart into the key elements that informed her life--growing up in the famed Drinkard family; the two romantic relationships that shaped the entirety of her adult life, with Robyn Crawford and Bobby Brown; her fraught relationship to her own Blackness and the ways in which she was judged by the Black community; her drug and alcohol addiction; and, finally, the shame that she carried in her heart, which informed every facet of her life. Drawing on hundreds of sources, Kennedy takes readers back to a world in which someone like Whitney simply could not be, and explains in excruciating detail the ways in which her fame did not and could not protect her. In the time since her passing, the world and the way we view celebrity have changed dramatically. A sweeping look at Whitney's life, Didn't We Almost Have It All contextualizes her struggles against the backdrop of tabloid culture, audience consumption, mental health stigmas, and racial divisions in America. It explores exactly how and why we lost a beloved icon far too soon" --